Exploration of morbidity, suicide and all-cause mortality in a Scottish forensic cohort over 20 years. Issue 4 (July 2020) - Rees, Cheryl; Thomson, Lindsay
Abstract : Background: Premature mortality among patients experiencing forensic care is high. This paper examines the morbidity and mortality of all Scottish high secure patients in 1992/1993 and followed up 20 years later through the context of recovery. Aims: To explore morbidity and delineate which patients are at greatest risk of premature mortality. To assess the extent of suicide and unnatural deaths. To establish which factors, if any, appear protective. Method: Health and mortality data were extracted from national data-sets and death categorised as premature or post-expected age. Standardised mortality ratios were calculated to explore natural, unnatural and suicide deaths with Cox regression conducted to explore baseline demographics and premature death. Results: During a mean follow-up of 21.1 years, 36.9% ( n = 89) died, at an average age of 55.6 years. Of these, 70.8% ( n = 63) died prematurely. Men lost on average 14.9 years and women 24.1 years of potential life. Five lives (5.6%) were lost by suicide and three (3.4%) by unnatural means. Conclusions: In contrast to other mainstream and forensic cohorts, high rates of suicide and accidental deaths were not apparent. Risk of premature mortality is high. A greater focus upon physical health by community and in-patient services is essential.